Long Term Follow-Up of Patients with Chronic Hepatitis C Treated with Alpha Interferon - Jane D Collier; Paul A Adams; Victor Feinman; Cameron Ghent; Helga Witt-Sullivan; Gerald Minuk; Mel Krajden; Jenny Heathcote (Canadian Journal of Gastroenterology)
Interferon alpha (IFN) treatment for chronic hepatitis C induces a sustained biochemical and virological response at six months after completing 24 weeks of therapy in approximately 10% of patients. The long term durability of this ‘sustained’ response is still controversial. The aim of this multicentre study was to assess the long term virological response in patients considered to have achieved a sustained biochemical response six months after completing IFN treatment. The majority (36 of 41) of the sustained responders identified had been treated for six months with IFN therapy. Twenty-nine of the 41 patients (70%) had undetectable hepatitis C virus (HCV) RNA after a mean follow-up of 38 months after cessation of treatment (range six to 92 months). All but one of those 29 individuals had normal serum alanine aminotransferase (ALT) levels. Of the 16 patients (out of 41) who had been tested for HCV RNA six months after treatment, HCV RNA remained undetectable in 14 (88%) at final follow-up. Serum ALT values in the 11 of 12 patients whose HCV RNA was positive at final follow-up were lower than pretreatment values, and in six cases were within the normal range. The long term sustained virological response in those considered a ‘sustained responder’ six months after receiving only six months of IFN is high. Measurement of ALT is an unreliable marker of sustained response to therapy.